2018
DOI: 10.1111/ejh.13083
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly changing myeloma epidemiology in the general population: Increased incidence, older patients, and longer survival

Abstract: The incidence of multiple myeloma is characterized by a steep increase with advancing age. Dramatic improvements in survival have been reported in clinical trials; however, elderly patients are generally underrepresented in these. The aims of this study are to review patterns of incidence and survival in multiple myeloma in the general population. We searched PubMed for population-based studies on trends in incidence and survival published between January 1, 2000 and June 30, 2017 and based on regional or nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 48 publications
4
98
0
5
Order By: Relevance
“…Multiple myeloma (MM) is a neoplasm of clonal plasma cells accounting for 1.8% of all cancers. MM is the second most common hematologic malignancy, with an estimated 30,280 new myeloma cases and 12,590 deaths in the U.S. in 2017 . In recent years, with novel therapies and a better understanding of the biology of MM, more patients achieve lasting remission, and there is an increased overall survival rate .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a neoplasm of clonal plasma cells accounting for 1.8% of all cancers. MM is the second most common hematologic malignancy, with an estimated 30,280 new myeloma cases and 12,590 deaths in the U.S. in 2017 . In recent years, with novel therapies and a better understanding of the biology of MM, more patients achieve lasting remission, and there is an increased overall survival rate .…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate of MM is approximately 50% 7 , which is nearly double what it was in the late 1980s. 8 The reason for the improved outcomes is a series of therapeutic advances that include the introduction of autologous stem cell transplants (ASCT), immunomodulatory drugs (IMiDs), and proteasome inhibitors (PIs), all of which are now first-line therapies.…”
Section: Introductionmentioning
confidence: 93%
“…8 The reason for the improved outcomes is a series of therapeutic advances that include the introduction of autologous stem cell transplants (ASCT), immunomodulatory drugs (IMiDs), and proteasome inhibitors (PIs), all of which are now first-line therapies. 79 Despite the success of these treatments in extending the overall survival (OS) by 6-10 years, depending upon age at diagnosis, most patients eventually relapse and become refractory to the therapies that they had received. 1012 The mechanisms by which patients develop resistance to these therapies are only partially understood and are thought to depend critically upon the BM microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…After year 2000, the introduction of more effective treatment agents in MM begun. [19][20][21] This includes the immunomodulators thalidomide and lenalidomide and the proteasome inhibitor bortezomib that were used increasingly during the latter calendar period, and were used in over 80% of all MM patients in Sweden in 2013. 31 Previous studies have shown that bortezomib can both inhibit growth of osteoclasts, and stimulate osteoblasts, thereby leading to bone healing in MM.…”
Section: Our Analyses On Different Subgroups Of Fractures In MM Patiementioning
confidence: 99%
“…Furthermore, to compare the effect of fractures on survival in MM before and after the introduction of novel treatment agents that have greatly improved survival in the MM patient population. [19][20][21]…”
Section: Introductionmentioning
confidence: 99%